1991
DOI: 10.1152/ajpheart.1991.261.6.h1913
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke extract attenuates endothelium-dependent arteriolar dilatation in vivo

Abstract: The purpose of this study was to examine the effects of cigarette smoke extract on endothelium-dependent and endothelium-independent dilatation of arterioles in vivo. Using intravital microscopy, we measured diameter of arterioles contained within the microcirculation of the hamster cheek pouch during suffusion with acetylcholine and nitroglycerin, before and after treatment with cigarette smoke extract. Under control conditions, acetylcholine and nitroglycerin produced dose-related dilatation of cheek pouch a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 0 publications
3
42
0
Order By: Relevance
“…These data suggest that at low concentrations gingipain RgpA stimulates the production of anti-inflammatory prostaglandins in the cheek pouch that partly counteract the edema-forming effects of the proteinase (23,25). However, at high concentrations of gingipain RgpA the salutary effects of these compounds are circumvented, in part, by local elaboration of bradykinin.…”
Section: ϫ6mentioning
confidence: 90%
See 2 more Smart Citations
“…These data suggest that at low concentrations gingipain RgpA stimulates the production of anti-inflammatory prostaglandins in the cheek pouch that partly counteract the edema-forming effects of the proteinase (23,25). However, at high concentrations of gingipain RgpA the salutary effects of these compounds are circumvented, in part, by local elaboration of bradykinin.…”
Section: ϫ6mentioning
confidence: 90%
“…This observation implies that the edema-forming effects of gingipain RgpA are catalytic site dependent. Lastly, indomethacin, at a concentration that inhibits cyclooxygenase in the cheek pouch (23,25), amplified macromolecular efflux elicited by a low (submaximal) concentration of gingipain Saline ( a Values are means Ϯ standard errors of the means; for each group, n ϭ 4 animals. GRgpA, gingipain RgpA; PI mixture, mixture of proteinase inhibitors consisting of aprotinin (5 g/ml), soybean trypsin inhibitor (100 g/ml), bestatin (10 M), and DL-2-mercapto-methyl-3-guanidinoethylthiopropanoic acid (10 M).…”
Section: ϫ6mentioning
confidence: 99%
See 1 more Smart Citation
“…In preliminary studies, I determined that infusion of indomethacin (10 mg/kg) alone for 30 min was associated with no visible leaky site formation or increase in clearance of FITC-dextran (data not shown). The concentration of indomethacin used in these studies was based on a previous study in my laboratory and has been previously shown to inhibit cyclooxygenase in the cheek pouch (24,27). .…”
Section: General Methods (I) Preparation Of Animalsmentioning
confidence: 99%
“…Active and passive exposure to cigarette smoke impairs NOSdependent reactivity of large and small peripheral vessels in animals ( Mays et al, 1999 ;Murohara, Kugiyama, Ohgushi, Sugiyama, & Yasue, 1994 ;Rubinstein, Yong, Rennard, & Mayhan, 1991 ) and humans ( Celermajer et al, 1996 ;Sumida et al, 1998 ). The cellular mechanism that contributes to impaired vascular function during exposure to cigarette smoke appears to involve oxygen-derived free radicals (Mays et al, 1999 ;Murohara et al, 1994 ;Ota et al, 1997 ).…”
Section: Consideration Of Previous Studiesmentioning
confidence: 99%